Kendala India dalam Upaya Mematuhi Konvensi Internasional Terkait Pemenuhan HAM Anak Perempuan dalam Pemberantasan Pernikahan Anak di India melalui Pemberlakuan UU PCMA - Putri, Alfiandia Vamyla Azhar; Basith Dir, Andi Akhmad (Journal of International Relations, 2020)
The practice of child marriage is one of the phenomena violated by human rights, but this practice still occurs in India. The Government of India has made efforts to eradicate child marriage by ratifying international agreements such as the Convention on the Rights of the Child (CRC), the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) and other treaties. To meet its requirements, India has agreed to these requirements in accordance with national law. But in the course of national law it did not work effectively. This research seeks to see what causes the ineffectiveness of efforts to eradicate child marriage through the implementation of national laws adopted from international agreements that have been agreed by India. Researchers use the theory of "Non-compliance" as a knife to analyze the above phenomenon. Where these factors become constrict for India to fulfill compliance with agreed international conventions.